Analisis dan Evaluasi Sistem Informasi Akuntansi Siklus Penjualan Dan Persediaan Bahan Baku - Arazy, Dito Rozaqi; Santika, Sisca (Magister Manajemen Universitas Wisnuwardhana, 2025)
Abstract. The current accounting information system is not only limited to a company or large-scale business, but it is highly recommended for MSMEs as small and medium businesses to organize an accounting information system. In the recording process, Micro, Small and Medium Enterprises (MSMEs) in Indonesia need to be supported by the use and management of good information systems. Information systems can facilitate business actors in monitoring and evaluating business processes and controlling business reporting. The purpose of the research to be achieved is to design or provide a definite picture of the accounting information system, specifically in the sales cycle and raw material inventory cycle. This type of research is qualitative research. This study uses primary data collected through survey methods, observations and in-depth interviews regarding the work cycle at the research site. The results of this study are expected to be input to MSMEs or businesses that will later build a system that can be the main foundation for businesses so that all cycles in it become more effective and efficient, and can make businesses competitive with other similar businesses.